The theoretical ways of using MICE Tourism as a tool of reducing seasonal limitations in Bukhara region - Kuvandikov Aziz Ravshanovich (Peerian Journals Publishing, 2025)
MICE industry ( The term “MICE” includes meetings, incentives, conferences and exhibitions) is one of the fastest growing segments within the tourism industry generating millions in revenues for cities and countries across the globe The aim of the paper is highlight the importance of MICE and to look at the future prospects of this industry in Uzbekistan to reduce seasonal limitations in Bukhara region
Keywords: Components of MICE Industry; Seasonality of destination; Uzbekistan